THE STUDY ON THE TRANSLATION IN NOKIA 6610 OWNER'S GUIDE : A Case Study of English-Indonesian Translation - Muhammad Rizal, S.H, - (2005)
The translated version of Nokia 6610 Owner's Guide as an example of vocative text is the object of this research. The aims of this research are (1) to find out about the translation method used in translating the Nokia 6610 Owner's Guide from English-Indonesian, (2) to find out about the 'other translation procedures' used by the translator of Nokia 6610 Owner's Guide, and (3) to find out about the translation quality of Nokia 6610 Owner's Guide. This research use qualitative method through several techniques. The first technique is by studying the original version of the Nokia 6610 Owner's Guide. The second one was conducting a library study, and the third one is by conducting a survey. The data then analysed and interpreted by using description, tables and a simple graphic. The result shows that the translation method used by the translator is literal translation method. Besides that, the translator also uses five 'other translation procedures' in her translation that are transference, naturalization, through-translation, shift or transposition and synonymy. About the translation quality based on the survey result, it shows that the translation quality of the Nokia 6610 Owner's Guide is relatively good.